Post-Resolution Treatment of Depositors At Failed Banks : Implications for the Severity of Banking Crises, Systemic Risk, and too-Big-To-Fail - Kaufman, George; Seelig, Steven (Washington, D.C. : International Monetary Fund, 2001)
Losses may accrue to depositors at insolvent banks both at and after the time of official resolution. Losses at resolution occur because of poor closure rules and regulatory forbearance. Losses after resolution occur if depositors' access to their claims is delayed or "frozen." While the sources and implications of losses at resolution have been analyzed previously, the sources and implications of losses after resolution have received little attention. This paper examines the causes of delayed depositors' access to their funds at resolved banks, describes how the FDIC provides immediate access, reports on a special survey of access practices in other countries, and analyzes the costs and benefits of delayed access in terms of both the effects on market discipline and depositor pressure to protect all deposits.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet